Stress partitioning between bcc and cementite phases discussed from phase stress and dislocation density in martensite steels. (1st January 2023) - Tsuchida, N.; Ueji, R.; Gong, W.; Kawasaki, T.; Harjo, S.
Abstract: The present study investigated the tensile deformation behavior of quenched and tempered martensite steels at various austenitization and tempering temperatures using in situ neutron diffraction experiments. Phase lattice strains in the bcc and cementite ( θ ) phases and dislocation structures in the bcc phase were analyzed. The phase lattice strain in bcc ( ε p h a s e b c c ) became almost stagnant after yielding as the tempering temperature increased. The phase lattice strain in θ increased linearly with an increase in the flow stress, independent of the austenitization and tempering temperatures. The stress partitioning between bcc and θ was confirmed after the yielding of bcc, which contributed to the work hardening. The phase stresses of bcc and θ and their stress partitioning improve the mechanical properties of martensite steels, which can be summarized by the systematic changes in phase lattice strain and dislocation properties due to the austenitization and tempering temperatures. Graphical abstract: Image, graphical abstract